Beyond early warning: towards greater granularity in the use of event-based surveillance for public health emergencies - C. J. McKnight; A. T. Aboushady; C. R. Lane (BMC Public Health)
Abstract Background The international health emergency caused by the emergence of the SARS-CoV-2 virus demonstrated the expanding usefulness of multi-country disease outbreak information gathered through event-based surveillance (EBS) as an extension beyond the main purposes of early warning, alert, and response (EWAR). In this article, previous events of multi-country outbreaks from 2010–2019 were reviewed for how EBS, within an expanded sphere of Epidemic Intelligence (EI), may help to enhance the understanding of outbreaks for a more timely and nuanced, multiple-point trigger approach to health emergencies. Methods The public, open-source database of ProMed reports were reviewed for the date of first notification on major outbreaks of infectious diseases and then compared for subsequent dates of any new, exceptional epidemiological findings (novel host, settings, transmission characteristics) as a determining factor for prolonged, multi-country events later acknowledged on the WHO disease outbreak news (DON) website, or by peer-reviewed journal publication if no related DON information became available. Results During the preceding decade, there was an ongoing occurrence of unexpected outbreaks requiring new information about previously unknown pathogens, such as MERS-CoV, and longstanding threats from multiple neglected tropical diseases. During these international outbreaks, key scientific insights about new host species, viral persistence, occurrence of human-to-human spread, and transmission setting, became known over the course of the response. Conclusion The timeliness between initial alerts of early outbreak detection and key epidemiological evidence about the emerging threat reached far beyond the first warning for the global community. To improve on the best knowledge available for an immediate response, it is recommended that further gathering and documentation from event-based surveillance is engaged to create a more complete assessment for uncontrollable infectious disease outbreaks and epidemics. Enhanced EBS (through modern tools, e.g., Epidemic Intelligence from Open Sources (EIOS) are critical for timely detection and response to such events.